(untitled) (PAAN Journal, 2025)
Do researchers know the ethical consideration factors and when to apply them in research? This paper uses secondary data sources to describe the various aspects of data editing disciplines and principles with ethical consideration of editing data in research in qualitative and quantitative research approaches. Through the past studies of, the ethical substructure of research contains dimensions on three levels: philosophical, pr-axis and reflexivity. The data editing process explores and reviews the data for consistency, detection of errors, and outliers and correction of errors, to improve the quality, accuracy and adequacy of the collected data thereby making it more suitable for the purpose for which the data was collected, such as the number and percentage of fields with errors detected to the total number of fields in the database. The data editing process is based on logic, common sense and adherence to a written procedure or editing guidelines for academicians, policymakers, and researcher for future research.